Visualizing Literary History First Step of designing a prototype for Litteraturbanken - Luo, Er (My University, 2015)
This project is about visualizing the Swedish literary history. To be more precise, the project develops a simple visual timeline website prototype of the Swedish literary history with Swedish authors as a basic step for the timeline webpage of the Litteraturbanken website. The project deals with how a timeline should be allocated, how different types of literary history and authors could be classified. During the development process, literature review has been made in order to set the basic guidelines for the timeline design. Different designs and tools of the visualization for timelines have been compared and analyzed based on discussion, web guidelines and visualization guidelines in order to inspire the design of this project. Different prototypes have then been made one after another for both internal comparing and continuous developing for this project. Two half-structured one-on-one interviews and one non-structured one-on-one interview have been made for getting the feedback from the latest prototype. Open discussion has been kept going during the development process for improving the quality of the timeline design. HTML codes and image processing have been studied in order to make a digital prototype. The final digital prototype is not a successful website design according to the interviewees' judgments. Therefore the best way of designing the timeline on the website stays uncertain after the finish of this project. The author's experience in being trapped into the guidelines and real data prototypes could be seen as a warning for other designers - keep guidelines and real data prototypes in mind, but never address them too much.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction